Branched-Chain Amino Acid Levels Are Related with Surrogates of Disturbed Lipid Metabolism among Older Men - Kujala, Urho M.; Peltonen, Markku; Laine, Merja K.; Kaprio, Jaakko; Heinonen, Olli J.; Sundvall, Jouko; Eriksson, Johan G.; Jula, Antti; Sarna, Seppo; Kainulainen, Heikki (Frontiers in Medicine, 2016)
Aims/hypothesis Existing studies suggest that decreased branched-chain amino acid (BCAA) catabolism and thus elevated levels in blood are associated with metabolic disturbances. Based on such information we have developed a hypothesis how BCAA degradation mechanistically connects to tricarboxylic acid (TCA) cycle, intramyocellular lipid storage and oxidation thus allowing more efficient mitochondrial energy production from lipids as well as providing better metabolic health. We analyzed whether data from aged Finnish men are in line with our mechanistic hypothesis linking BCAA catabolism and metabolic disturbances. Methods Older Finnish men enriched with individuals having been athletes in young adulthood (n=593; mean age 72.6 ± 5.9 years) responded to questionnaires, participated in a clinical examination including assessment of body composition with bioimpedance and gave fasting blood samples for various analytes as well as participated in a 2 hour 75 g oral glucose tolerance test. Metabolomics measurements from serum included BCAAs (isoleucine, leucine and valine). Results Out of the 593 participants 59 had previously known type 2 diabetes, further 67 had screen-detected type 2 diabetes, 127 IGT and 125 IFG while 214 had normal glucose regulation. There were group differences in all of the BCAA concentrations (p≤0.005 for all BCAAs), such that those with normal glucose tolerance had the lowest and those with diabetes mellitus had the highest BCAA concentrations. All BCAA levels correlated positively with body fat percentage (r=.29 - .34, p<.0001 for all). Expected associations with high BCAA concentrations and unfavorable metabolic profile indicators from metabolomics analysis were found. Except for glucose concentrations, the associations were stronger with isoleucine and leucine than with valine. Conclusions/interpretation The findings provided further support for our hypothesis by strengthening the idea that the efficiency of BCAA catabolism may be mechanistically involved in the regulation of fat oxidation thus affecting the levels of metabolic disease risk factors.